Determinants of the Social Media Influence on the Consumers’ Travel Decision Making Process - Hossain, Noor; Kundu, Amit (International Journal of Engineering and Management Research, 2025)
Purpose – The purpose of this study is to ascertain how customers use social media for travel-related decision making at their three stages of the travel namely, pre-travel, during the travel and the post travel decision making. Design/Methodology/Approach – After analyzing the relevant literature, a quantitative investigation was carried out using structured questionnaire. A questionnaire with identified items in the three stages was used to gather the primary data from the consumers who have used social media for their travel related decision making, and a statistical package was used to analyze the findings. Findings – A theoretical framework was developed and the developed model was validated by determining the elements influencing social media use for travel-related reasons at the three stages of decision making. Research Limitations/Implications – The respondents were chosen solely from the state of West Bengal, and the sample was not chosen at random. The study might have a difficulty with generalization, particularly when it comes to marketplaces with significantly distinct cultural traits. Practical Implications – The study's conclusions might help researchers and industry professionals comprehend social media and Web 2.0 technologies and how they affect customers in their travel related decision making. Originality/Value – Social media use is one of the main factors influencing consumer behavior and travel marketing in recent years. Understanding these trends and how they affect consumer behavior is crucial because they could affect how travel-related information is distributed and made accessible.